Immigrants or children? The expulsion of unaccompanied minors from two California towns. (2018) - Ruiz, Olivia
This article analyses civic mobilisations to oppose and welcome the arrival of unaccompanied children and adolescents from Central America and Mexico to two California towns in the summer of 2014. At first glance, the mobilisations appear to adhere to protectionist and humanitarian positions that have defined much recent debate concerning international migration. Digging deeper, however, it becomes clear that the dispute centred on disagreements concerning the young migrants' identity - on the one hand, as immigrants, on the other, as children and the association of both ascriptions with risk and vulnerability. To make their claims, contesting camps in the dispute drew on narratives about immigration as well as narratives about children and childhood. Ultimately, arguments that the young Central Americans and Mexicans posed a risk trumped appeals to their vulnerability as children. This article attempts to explain why and how that occurred.